2018
DOI: 10.1097/mpa.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Insulin Secretion Ability With Microcirculation Evaluated by Contrast-enhanced Ultrasonography in Pancreas Transplantation

Abstract: These results suggest that delta-Tp(P-V)24 hours affects insulin secretion after Tx. Contrast-enhanced ultrasonography is useful in predicting endocrine function of the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our previous report showed that a decrease in peripheral tissue perfusion immediately after pancreas transplantation, as evaluated by CEUS, resulted in the deterioration of the pancreatic graft endocrine function. 18,19 Changes in these 3 parameters may indicate a severe reduction in the peripheral tissue perfusion of the pancreatic graft due to dehydration and/or hypercytokinemia. In addition, a previous canine FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report showed that a decrease in peripheral tissue perfusion immediately after pancreas transplantation, as evaluated by CEUS, resulted in the deterioration of the pancreatic graft endocrine function. 18,19 Changes in these 3 parameters may indicate a severe reduction in the peripheral tissue perfusion of the pancreatic graft due to dehydration and/or hypercytokinemia. In addition, a previous canine FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated the usefulness of contrast-enhanced ultrasonography (CEUS) after pancreas transplantation 18 and demonstrated that tissue perfusion of the pancreatic graft, as evaluated by CEUS immediately after transplantation, was correlated ΔCPR (as a parameter reflecting the endocrine function) at 1 month after transplantation. 19 Because the tissue perfusion in the pancreatic graft evaluated by CEUS immediately after transplantation can be expected to be significantly affected by the donor condition, it raised a clinical question: what donor factors have an impact on ΔCPR. In the present study, we investigated the donor factors that affect ΔCPR, as a parameter reflecting the endocrine function after pancreas transplantation.…”
mentioning
confidence: 99%
“…For example, with regards to graft thrombosis, one report shows the efficacy of contrast-enhanced ultrasonography for thrombosis detection. 17 Postoperative monitoring of the blood flow in the pancreas graft is considered important, as early detection may enable pancreas graft rescue by interventional radiological therapy. [18][19][20] However, duodenal graft perforation is reportedly associated with both immunological rejection and technical factors, such as poor blood supply, kinking of the intestinal anastomosis, and high pressure of the graft duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduction of pancreas graft loss will require preventative measures to address each cause. For example, with regards to graft thrombosis, one report shows the efficacy of contrast‐enhanced ultrasonography for thrombosis detection 17 . Postoperative monitoring of the blood flow in the pancreas graft is considered important, as early detection may enable pancreas graft rescue by interventional radiological therapy 18–20 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason why there were no episodes of thrombosis or perforation of the graft duodenum in the PD group in our study, despite the difficulty of vascular anastomosis, was the relatively better tissue perfusion in the early period after transplantation. Aida et al [23]. reported that early perioperative graft pancreatic tissue perfusion, as assessed by contrast-enhanced ultrasonography, tended to be better in younger donors.…”
Section: Discussionmentioning
confidence: 99%